Pelaksanaan Pelatihan Tazkiyyatunnafs terhadap Islamic Religious Coping Mahasantri Pesma Unisa Bandung - Nur Rohmah; Anugerah Anugerah; Endang Pujiastuti; Aef Herosandiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of self-control training through tazkiyyatunnafs held at PESMA UNISA Bandung for five months on the increase in Islamic Religious Coping of Students. The method used is quantitative with a quasi-experimental research design pre-test-post-test two-group design. The results of this study indicate that Tazkiyyatun-nafs training has significantly increased the average Islamic Religious Coping scores for PESMA UNISA Bandung students from an average of 80.4% to 86.2%. In conclusion, self-control training through tazkiyyatunnafs has effectively had a significant effect on Islamic Religious Coping owned by female students. Keywords: Islamic Religious Coping, Student Islamic Boarding Schools, Tazkiyyatunnafs